Pattern of Traumatic Brain Injury at King Abdulaziz University Hospital - Mohammed Bangash; Ahmad T. Alshareef (Journal of King Abdulaziz University: Medical Sciences, 2023)
Traumatic brain injury is a common problem in society leading to morbidity and mortality. This study describes pattern of traumatic brain injury at King Abdulaziz University Hospital, and identify the demographic and clinical factors affected in the survivors' hospital length of stay. A retrospective study performed in January 2003 till January 2009. The incidence of traumatic brain injury requiring admission in relation to annual emergency room is 75/100,000 patients; mean age is 9.5 ± 4 years with ~81% of injuries occurring at < 30 years. Severe traumatic brain injury accounts for 15.1% of cases, whereas moderate traumatic brain injury accounts for 10.4% and mild traumatic brain injury accounts for 74.5%. Mechanisms of injuries: 46.5%, falling from a height, 26.7% motor vehicle collisions, 10.4% pedestrian-vehicle collisions and 10.4% assault victims. Factors affecting the hospital length of stay: Admission Glasgow Coma Scale (p < 0.001), loss of consciousness p < 0.001, presence of motor weakness p < 0.001, female gender p < 0.03, patients' age p < 0.001 and the nationality p < 0.001. Characteristics of traumatic brain injury: Young age, the mechanism of injury (mainly falls) and type of injury (mainly concussion). Tentatively, the patients' length of stay is predicted on the demographic and clinical data.